Implementasi Pembelajaran PAI dalam Pembentukan Karakter Kepribadian Yang Islami - Lulu Khairunnisa; Achmad Ruslan Afendi; Adrian Maulana; Rahmatul Muthmainnah (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2023)
Abstract: The purpose of this research is to find out the implementation of pie learning in the formation of Islamic character. The method used is a qualitative descriptive research method in which research data is obtained from credible sources, including books, scientific journals and other publications that provide data as a source for this research. The results of the discussion in this study are that Islamic religious education is very influential in character building, where today we meet lots of students who do not have bad personality traits, for example fighting parents or teachers, getting drunk, committing violence and others. Character formation can occur from with in, namely within the family and from outside, namely from the surrounding environment, for example neighbors or at education/school. Therefore the importance of character education is to clean up bad morals and instill good values in students so that they get closer to Allah and happiness both in this world and the hereafter. Keywords: keywords Education, character, Islam